Intra- and inter-annual uranium concentration variability in a Belizean stalagmite controlled by prior aragonite precipitation: A new tool for reconstructing hydro-climate using aragonitic speleothems. (1st October 2016) - Jamieson, Robert A.; Baldini, James U.L.; Brett, Marianne J.; Taylor, Jessica; Ridley, Harriet E.; Ottley, Chris J.; Prufer, Keith M.; Wassenburg, Jasper A.; Scholz, Denis; Breitenbach, Sebastian F.M.
Abstract: Aragonitic speleothems are increasingly utilised as palaeoclimate archives due to their amenability to high precision U–Th dating. Proxy records from fast-growing aragonitic stalagmites, precisely dated to annual timescales, can allow investigation of climatic events occurring on annual or even sub-annual timescales with minimal chronological uncertainty. However, the behaviour of many trace elements, such as uranium, in aragonitic speleothems has not thus far been as well constrained as in calcitic speleothems. Here, we use uranium concentration shifts measured across primary calcite-to-aragonite mineralogical transitions in speleothems to calculate the distribution coefficient of uranium in aragonitic speleothems (derived DU  = 3.74 ± 1.13). Because our calculated DU is considerably above 1 increased prior aragonite precipitation due to increased karst water residence time should strongly control stalagmite aragonite U/Ca values. Consequently, uranium concentrations in aragonitic speleothems should act as excellent proxies for effective rainfall. We test this using a high-resolution ICP-MS derived trace element dataset from a Belizean stalagmite. YOK-G is an aragonitic stalagmite from Yok Balum cave in Belize with an extremely robust monthly-resolved chronology built using annual δ 13 C cycles. We interpret seasonal U/Ca variations in YOK-G as reflecting changes in the amount and seasonality of prior aragonite precipitation driven by variable rainfall amounts. The U/Ca record strongly suggests that modern drying has occurred in Belize, and that this drying was primarily caused by a reduction in wet season rainfall. This is consistent with published stable isotope data from YOK-G also very strongly suggesting modern rainfall reductions, previously interpreted as the result of southward ITCZ displacement. Our results strongly suggest that U/Ca values in aragonitic speleothems are excellent proxies for rainfall variability. This new tool, combined with the exceptional chronological control characteristic of aragonitic stalagmites and the high spatial resolution afforded by modern microanalytical techniques, should facilitate the construction of new exquisitely resolved rainfall records, providing rare insights into seasonality changes as well as long-term changes in local recharge conditions.